Money Demand in an EU Accession Country: A VECM Study of Croatia - Max Gillman; Dario Cziráky (Cardiff University, Cardiff Business School, 2005)
The paper estimates the money demand in Croatia using monthly data from 1994 to 2002. A failure of the Fisher equation is found and adjustment to the standard money demand function is made to include the inflation rate as well as the nominal interest rate. In a two-equation cointegrated system, a stable money demand shows rapid convergence back to equilibrium after shocks. This function performs better than an alternative using the exchange rate instead of the inflation rate, as in the pass-through literature on exchange rates. The results provide a basis for inflaton rate forecasting and suggest the ability to use inflation targeting goals in transition countries during the EU accession process. Finding a stable money demand also limits the scope for central bank inflation bias.
Keywords: 330